What does the future hold for novel intravascular imaging devices: a focus on morphological and physiological assessment of plaque. (2nd December 2017) - Katagiri, Yuki; Tenekecioglu, Erhan; Serruys, Patrick W.; Collet, Carlos; Katsikis, Athanasios; Asano, Taku; Miyazaki, Yosuke; Piek, Jan J; Wykrzykowska, Joanna J.; Bourantas, Christos; Onuma, Yoshinobu
ABSTRACT: Introduction : It is well recognized that a lesion that does not cause a hemodynamically significant stenosis can trigger a sudden cardiac event through plaque rupture. As a diagnostic tool, intravascular imaging was developed to circumvent limitations of coronary angiography; however, none of the intravascular imaging devices are individually able to provide complete assessment of the plaque morphology, geometry, physiology and biology. Therefore, over the past few years an effort was made to develop hybrid intravascular imaging catheters to provide more complete evaluation of coronary plaque pathobiology. Areas covered : This paper aims to give an overview of the recent developments on 1) single-modality intravascular imaging devices; 2) hybrid intravascular imaging devices and 3) the hemodynamic analysis in models reconstructed from the fusion of intravascular imaging and angiographic data. Expert commentary : Within five years, most of the hybrid imaging techniques which are now in pre-clinical phase will be utilized in the clinical arena, as NIRS-IVUS. Software for online blood simulation is likely to be developed that will enable ESS calculation while the patient is in the catheterization laboratory.